Investigating legal information in commercial websites: the Terms and conditions of use in different varieties of English - Scarpa, Federica (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The Terms and conditions of use which are embedded in commercial websites provide a standardised legal model based in common law which exemplifies the increasingly influential role that English plays in international and intercultural commercial and legal settings, but also how deeply rooted legal knowledge is in socio-cultural values and national cultures. Using a small monolingual corpus of Terms and conditions of use drafted in English and embedded in the commercial websites from different countries of origin and legislations based both on common law and civil law, the paper investigates the extent to which different layout/content and language features are displayed by: (1) ELF Terms and conditions translated from different languages/legislations, and (2) ENL non-translated Terms and conditions drafted in different ‘core’ varieties of English. The aim is to show that the English intralingual variation of this highly structured and conventionalised legal format reflects in fact the existing disparities in legal practice among various national legislations, even among systems belonging to the common law family. International legal models such as the one investigated should consequently be considered as “globally-relevant STs” (Adab, 1998, p. 224), i.e. flexible text formats that have been adopted by most countries but at the same time allow for local socio-cultural aspects to influence the construction of legal discourse.